Still Counting the Dead: Survivors of Sri Lankas Hidden War
The tropical island of Sri Lanka is a paradise for tourists, but in 2009 it became a hell for its Tamil minority, as decades of civil war between the Tamil Tiger guerrillas and the government reached its bloody climax. Caught in the crossfire were hundreds of thousands of schoolchildren, doctors, farmers, fishermen, nuns and other civilians. And the government ensured through a strict media blackout that the world was unaware of their suffering. Now, a UN enquiry has called for war-crimes investigations. Those crimes are recounted here to the wider world for the first time in sobering, shattering detail.